Comparison Between Intra Vitreal Bevacizumab and Triamcinolone in Reducing Macular Thickness in Central Retinal Vein Occlusion - Muhammad Sajid Khan, Tariq Khan, Farooq Khan, Ahmed Jamal Khan, Maqsood Ahmad, Ubaid Ullah (Pakistan Journal of Medical & Health Sciences, 2023)
Objectives: To compare the effect of intra vitreal bevacizumab (IVB) and intra vitreal triamcinolone (IVT) in reducing macular thickness in central retinal vein occlusion. Methods and Materials: This quasi experimental study was conducted at Department of Ophthalmology, Hayat Abad Medical Complex Peshawar in the period from 01 January 2020 to 30 June 2020. Total 40 patients presented with central retinal vein occlusion (CRVO). Patients were divided into two groups, group A received IVB treatment and group B received IVT treatment. The patients were followed up on 6th month post treatment. The primary outcomes of the study were visual acuity and reduction in macular thickness on OCT post treatment. Results: 40 patients were enrolled in the study. The mean age of patients was 60.70±15.49 in group A and in group B 60.40±12.83. There were 13 males and 7 females in group A and 12 males and 8 females in group B. Mean VA at baseline was 1.0825±0.25 logMAR in group A and 0.9745±0.29 logMAR in group B. Mean macular thickness at baseline was 625.40±47.15 µm in group A and 642.05±44.23 µm in group B. Mean VA at 6th month post treatment follow up was 0.4195±0.23 logMAR in group A and in group B was 0.4960±0.27 logMAR. At 6th month follow up macular thickness was 261.80±26.269 µm in group A and 263.80±22.209 µm in group B. Conclusion: Intravitreal injections of bevacizumab and triamcinolone have shown a reduction in macular edema in CRVO patients along with improvement in visual acuity. Keywords: Bevacizumab, Triamcinolone, Macular Edema, Central Retinal Vein Occlusion, Visual Acuity